5x-3+2x+5=9x+6

Simple and best practice solution for 5x-3+2x+5=9x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3+2x+5=9x+6 equation:


Simplifying
5x + -3 + 2x + 5 = 9x + 6

Reorder the terms:
-3 + 5 + 5x + 2x = 9x + 6

Combine like terms: -3 + 5 = 2
2 + 5x + 2x = 9x + 6

Combine like terms: 5x + 2x = 7x
2 + 7x = 9x + 6

Reorder the terms:
2 + 7x = 6 + 9x

Solving
2 + 7x = 6 + 9x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-9x' to each side of the equation.
2 + 7x + -9x = 6 + 9x + -9x

Combine like terms: 7x + -9x = -2x
2 + -2x = 6 + 9x + -9x

Combine like terms: 9x + -9x = 0
2 + -2x = 6 + 0
2 + -2x = 6

Add '-2' to each side of the equation.
2 + -2 + -2x = 6 + -2

Combine like terms: 2 + -2 = 0
0 + -2x = 6 + -2
-2x = 6 + -2

Combine like terms: 6 + -2 = 4
-2x = 4

Divide each side by '-2'.
x = -2

Simplifying
x = -2

See similar equations:

| 3=1.2+-0.2y | | 14x^3-8x^2+18x= | | -25=5(a-8) | | (x-30)(x-30)(x-30)=540 | | 3x+4+3x-6=8x+4 | | -14=-6+4e | | 29=-x+7x-1 | | 3x+5+3x-6=10x-2 | | 2=1.2+-0.2y | | 30x+5=64 | | 1=1.2+-0.2y | | 42x^2-480x-2463=0 | | 120+.30x=80+.50x | | x+2y-1=6x-9 | | -4m+13=9 | | 3+6cosx=0 | | u^2+u-21=0 | | -6m-13=163 | | 6+0.4x=18+.02 | | 4(-2m-5)+8m=-15 | | 287+49m+7n=-64+4m-2n | | 322-(-159)+10-159+78= | | 39x^2-482x-2464=0 | | X+(x+3)=61 | | 2x-4=3x+12 | | .06+.04x=18+.02 | | 8(b+7)=0 | | y=-4*-4+2*-4-7 | | 36y^7+4y^4= | | 4.5/g+2=3/0.5g-1 | | 12-5+x=5+8-2 | | 8x+2y+2=180 |

Equations solver categories